2017
DOI: 10.1063/1.5011616
|View full text |Cite
|
Sign up to set email alerts
|

The effect of differences rainfall data duration and time period in the assessment of rainwater harvesting system performance for domestic water use

Abstract: Abstract.One of the attempts to tackle the problem in water resources is to exploit the potential of rainwater volume with rainwater harvesting (RWH) system. A number of rainfall data required for analyzing the RWH system performance. In contrast, the availability of rainfall data is occasionally difficult to obtain. The main objective of this study is to investigate the effect of difference rainfall data duration and time period to assess the RWH system performance. An analysis was conducted on the rainfall d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…where m = increase in water price per year (%), i = discount rate per year (%), k = increase in maintenance and operational costs per year (%), Smin and Smax = minimum and maximum tank capacity, Npop,min and Npop,max = minimum and maximum number of occupants. Constraint (12) is the value of the benefit-cost ratio, BCR. The project lifetime is calculated for T = 10 years so that the BCR value should be greater than 1 at the 10 th year.…”
Section: Optimization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where m = increase in water price per year (%), i = discount rate per year (%), k = increase in maintenance and operational costs per year (%), Smin and Smax = minimum and maximum tank capacity, Npop,min and Npop,max = minimum and maximum number of occupants. Constraint (12) is the value of the benefit-cost ratio, BCR. The project lifetime is calculated for T = 10 years so that the BCR value should be greater than 1 at the 10 th year.…”
Section: Optimization Modelmentioning
confidence: 99%
“…In several big cities in Indonesia, such as Bandung, Jakarta, and other big cities, many people still have difficulty getting access to clean water [11][12][13]. One alternative to help meet this need for clean water is through the Rainwater harvesting (RWH) system [11][12][13]. RWH can also provide additional benefits to reduce runoff [1].…”
Section: Introductionmentioning
confidence: 99%
“…These models can also help in predicting the future performance of the system under different scenarios [ 56 , 61 , 62 ]. These models use different time series data (hourly, daily or monthly) [ [63] , [64] , [65] ]. Daily time series provide similar results to hourly time series, while monthly time series generate inaccurate results [ [63] , [64] , [65] ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have discussed non-structural efforts to reduce the flood risk in the Upper Citarum River, such as those of Juliana et al [34], Wijaya [39], and Kusuma et al [35]. Based on 15 years of rainfall data records, Juliana et al [34] discussed the feasibility of implementing a rain harvesting program to reduce run-off in the Upper Citarum River.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have discussed non-structural efforts to reduce the flood risk in the Upper Citarum River, such as those of Juliana et al [34], Wijaya [39], and Kusuma et al [35]. Based on 15 years of rainfall data records, Juliana et al [34] discussed the feasibility of implementing a rain harvesting program to reduce run-off in the Upper Citarum River. Kusuma et al [21] concluded that the lack of reliability of hydrology, hydrometeorology, and land-use change data was becoming a significant barrier to correctly estimating the flood characteristic trends of the Upper Citarum River.…”
Section: Introductionmentioning
confidence: 99%